MIGRATION POVERTY AND SLAVERY OF HUMAN BEING (STUDY IN PSYCHOLOGY PERSPECTIVE) - Fahmi, Reza (Universitas Islam Negeri Imam Bonjol Padang, 2018)
The research aims: (1) Describing a migration of poverty from Indonesian people. (2) Describing a slave of human being. (3) The correlation between migrations of poverty and slavery of human being. The research used mixing methods as an approach. The population of the study was about 128 people. But only 97 people involved in this research. The simple random sampling was using as a technique of sampling. The data collected with psychological scale, data documentation, depth interview and Focus Group Discussion). The research found that: firstly, the average of the mean and percentage of migration poverty were categories high. It means that most of Indonesian people who migrate as a worker are coming from lower class society. Secondly, the average mean and percentage of slavery of human being high. It means that most of Indonesia people could not have bargaining power for doing their job. Then, there are correlation between migrant poverty and slavery of human being involved Indonesian worker.